DETERMINATION OF TENDENCIES IN THE RESEARCH OF PAIN SYNDROME AFTER TONSILLECTOMY (PILOT RESEARCH) - V. I. Popadyuk; I. V. Kastyro; A. V. Zalizko (Acta Biomedica Scientifica)
We realized dynamic control of pain syndrome intensity after toлsillectomy in. 24 patients. In. 2 hours after the operation 80 % of patients had. medium, and. strong рат, in 1 day 25 % had. weak рат and. 50 % - medium рат. On the 3rd day 54 % of patients had. weak pain or didn't have pain syndrome at all. Determination of pathogenetic variant of pain syndrome: in 2 hours after the operation 62,5 % of patients had. psychogenic pain syndrome, 25 % - neurogenic; in 1 day 41,7 % had. psychogenic and. 33,3 % - neurogenic; in 3 days 41,7 % had. somatogenic pain syndrome, 29,2 % - psychogenic and. 21 % didn't have pain syndrome. It's necessary to diagnose pain syndrome at the early stage after tonsillectomy with help of analogue scales of pain evaluation. It seems prospective to determine pathogenetic variant of acute pain with help of verbal-color scale and. elaboration of analgetic therapy, that is corresponding to the pathogenetic variant, for the patients after tonsillectomy.